(untitled) (Journal of the College of Languages (JCL), 2012)
Reading is an interactive process that goes on between the reader and the text, resulting in comprehension. The text presents letters, words, sentences, and paragraphs that encode meaning. The reader uses knowledge, skills, and strategies to determine what that meaning is. Reading comprehension is much more than decoding; it results when the reader knows which skills and strategies are appropriate for the type oftext, and understands how to apply them to accomplish the reading purpose.Reading comprehension is important because without it reading is nothing more than tracking symbols on a page with your eyes and sounding them out leaving the reader with no information. Instead of promoting traditional approaches, reading should be taught in a more interactive and communicative manner. In this light, this study investigates the difficulties faced by engineering students in reading comprehension in a university setting where the medium of instruction and communication is not English, but where students are required to read textbooks in English. The participants are selected from College of Engineering/ University of Al-Mustansiriya to take the test. However, a standardized test is used to show the students’ difficulties in reading comprehension. Two passages are used in the test, the first one is concerned with their specialization in engineering while the second is concerned with general topics. Data analysis is conducted through using one sample T. test and percentages statistical methods. Results of this study reveal that engineering students have great difficulties in reading comprehension since most of them have not succeeded in the test. Reasons behind such results have been illustrated and certain suggestions have been given to be useful for both teachers and students of scientific fields especially engineering.